2013
DOI: 10.1016/j.biopsych.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pattern of Perineuronal Nets in the Human Prefrontal Cortex and Their Deficit in Schizophrenia

Abstract: Background Perineuronal nets (PNNs) are extracellular matrix structures that enwrap many neurons in the brain. They regulate the postnatal experience-dependent maturation of brain circuits and maintain their functional integrity in the mature brain by stabilizing their synaptic architecture. Methods Eighty-six postmortem human brains were included in this study. We used Wisteria Floribunda agglutinin histochemistry to visualize PNNs to investigate whether the densities of PNNs in the prefrontal cortex (PFC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
272
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 253 publications
(296 citation statements)
references
References 61 publications
22
272
1
1
Order By: Relevance
“…In the comparison subjects, qualitative analyses revealed that PV neurons and PNNs (identified by WFA labeling or aggrecan immunoreactivity) were present in greatest density in layer 3 of DLPFC area 9 (Figure 1a-1), consistent with prior findings (Hashimoto et al, 2003;Mauney et al, 2013). Many PV neurons were surrounded by PNNs and the majority of PNNs surrounded PV neurons; however, some …”
Section: Pv and Pnn Labeling Is Prominent In Dlpfc Layersupporting
confidence: 85%
See 4 more Smart Citations
“…In the comparison subjects, qualitative analyses revealed that PV neurons and PNNs (identified by WFA labeling or aggrecan immunoreactivity) were present in greatest density in layer 3 of DLPFC area 9 (Figure 1a-1), consistent with prior findings (Hashimoto et al, 2003;Mauney et al, 2013). Many PV neurons were surrounded by PNNs and the majority of PNNs surrounded PV neurons; however, some …”
Section: Pv and Pnn Labeling Is Prominent In Dlpfc Layersupporting
confidence: 85%
“…3b), indicating that cells with normal levels of PV protein are readily detectable. Thus, prior reports of apparently lower PV cell density (Beasley et al, 2002) are likely due to lower levels of PV protein and reported losses of PNNs (Mauney et al, 2013) are not likely due to loss of PV neurons.…”
Section: Discussion Pv Cells and Pnns Are Normal In Density But More mentioning
confidence: 78%
See 3 more Smart Citations